Leber’s hereditary optic neuropathy and multiple sclerosis: overlap between mitochondrial disease and neuroinflammation - Golbarg Rahimi; Mackenzie Silverman; Maeve Lucas; Lilia Kazerooni; Mariam M. Yousuf; Saba Jafarpour; Saba Jafarpour; Jonathan D. Santoro; Jonathan D. Santoro (Frontiers in Neurology)
Although Multiple sclerosis (MS) and Leber hereditary optic neuropathy (LHON) have distinct pathophysiological mechanisms, they are both neurodegenerative conditions that involve mitochondrial dysfunction. MS is an autoimmune disease that is characterized by demyelination and neuroinflammation; and LHON is a mitochondrial disorder predominantly affecting the optic nerves, resulting in severe vision loss. Recent studies have highlighted the coexistence of these two conditions, particularly in females, suggesting that mitochondrial variants in LHON may predispose individuals to develop MS or affect its progression. Similar to MS, LHON-MS presents with visual impairment, neurological deficits, white matter lesions, and brain atrophy, which further supports a shared underlying pathophysiology. While MS is not inherently a mitochondrial disorder, its neuroinflammatory processes can lead to mitochondrial dysfunction. Reciprocally, mitochondrial impairment may be exacerbated in LHON-MS. Therefore, the role of mitochondrial dysfunction in these diseases is central, with impaired mitochondrial function contributing to cellular damage and neuroinflammation. This review explores the intersections of MS and LHON, emphasizing the need for further research to better understand mitochondrial dysfunction in these disorders.